Surgical management of pneumomediastinum in the COVID-19 patient. Issue 12 (22nd December 2022) - Abou-Abdallah, Michel; Dewhurst, Samuel; Dunne, Henry; Irune, Ekpemi
Abstract : As the SARS-CoV-2 virus continues to infect millions of people worldwide, the medical profession is seeing a wide range of short-term and long-term complications of COVID-19. One lesser-known complication is that of pneumomediastinum. This is a rare, but significant, complication defined by the presence of air in the mediastinum with an incidence of 1.2 per 100 000. Described mortality rate is 30%, increasing to 60% in patients with concomitant pneumothoraces. Management of pneumomediastinum is typically conservative, but in cases of extensive subcutaneous emphysema, cardiac or airway compression, life-saving surgical decompression is necessary. We report a case of pneumomediastinum secondary to COVID-19, requiring a surgical approach not described in pneumomediastinum secondary to COVID-19. The case demonstrates the importance of prompt diagnosis and management, as well as the potential for good clinical outcome in selected patients.